«I had a keen strong passion for history». The figure of Father Luigi Luchini and the donation of materials from Bedriacum to the Archaeological Museum of Cremona (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
In the history of the 19th-century archaeological research in Calvatone-Bedriacum, Father Luigi Luchini, born in Milan but lived for most of his life in the territory of the Diocese of Cremona, played a central role. The Ala Ponzone Civic Museum keeps interesting archival documents to reconstruct the first findings of the vicus and the vicissitudes of the collection that originated from them.
Keywords: Luigi Luchini; Bedriacum; collection; Archaeological Museum of Cremona; archive